Information technology prioritization, in merger integration: A grounded theory approach - RAIKAR, Sandesh Dayanand (Institutional Knowledge at Singapore Management University, 2017)
This exploratory study, examines the significance of Information Technology (IT) Prioritization during the due diligence phase, in a merger integration scenario. In a world where firms are becoming increasingly dependent on information systems and technology, IT continues to play a progressively significant role within organizations. There is growing literature, on the increasing importance of IT in the business environment. However, till date, neither has there been a study regarding the role and impact of IT prioritization and IT integration schedule on the overall synergy savings, nor is there a study on the relationship between IT prioritization and the achievement of the technology priorities of the firm. This study, explores the concept of IT prioritization as an independent variable, and reviews its impact on dependent variables such as IT synergy savings, overall synergy savings, IT integration budget and the achievement of the technology priorities of the firm. The study intends to keep both academicians and practitioners informed, on the above topic. A systematic grounded theory approach is used as the method of research, as it is well-suited to the exploratory nature of this study. This approach allows the analysis, of both qualitative and quantitative data. The qualitative data is provided by the indepth interviews, while the online survey provides the quantitative data. This study draws on the lived experience of senior executives and seasoned practitioners, in the field of M&A integration. The said individuals, are from diverse industries and geographies. The outcome of this research indicates that IT prioritization during the due diligence phase, has a positive relationship with (1) the overall synergy savings, (2) the IT integration budget, and (3) the achievement of the technology priorities of the firm. The results also indicate a negative relationship between integration schedule delay and overall synergy savings. An interesting finding is that firms with low information intensity, deliver highly amplified overall synergy savings, as compared to high information intensity firms, under similar conditions of IT prioritization. The most compelling finding of this research is that IT prioritization matters, and it makes a significant and direct contribution, to the success of the merger integration effort.